STRATEGI PEMASARAN SAYURAN HIDROPONIK - Sumarni B; Siti Wardah; Rasdiana Mudatsir (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Kelautan Universitas Bangka Belitung, 2024)
This study intends to design and determine a marketing strategy for hydroponic vegetable at CV. Ichira Hydro Farm, Bialo Hydroponic House, and Pallangga Hydroponic House. This study employs quantitative methods. Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), and SWOT analysis are three methods of data analysis used to develop and decide on marketing strategy for hydroponic vegetable. The study's findings indicate that seven techniques are employed to sell hydroponically grown crops, including : (1) improve product quality so that consumer trust and interest increases, (2) improve the quality of service for consumers in marketing activities both in buying and selling transactions and in terms of payments, (3) enhance the quality of packaging by employing eco-friendly packaging that is branded and features product logos to establish a perception in the minds of customers, (4)expanding the product marketing network by optimizing the use of social media as a means of promotion and marketing, (5) increase marketing collaboration with similar companies, (6) Selling prices are competitive and in accordance with the quality of the vegetable products produced, and (7) increasing the volume of availability hydroponic vegetable products. Keywords: strategy, marketing, hydroponic vegetables